CRMP2–Neurofibromin Interface Drives NF1-related Pain. (15th June 2018) - Moutal, Aubin; Sun, Li; Yang, Xiaofang; Li, Wennan; Cai, Song; Luo, Shizhen; Khanna, Rajesh
Highlights: CRMP2/neurofibromin interface controls increased voltage-gated Ca 2+ channel CaV2.2 currents after Nf1 gene editing. CNRP1 peptide reversed voltage-gated Na + channel NaV1.7 currents and DRG excitability after Nf1 gene editing. Membrane localization of CaV2.2 and NaV1.7 is controlled by CRMP2/neurofibromin interface. Targeting CRMP2/neurofibromin interface reversed NF1-related nociceptive behavior without motor impairment. Abstract: An understudied symptom of the genetic disorder Neurofibromatosis type 1 (NF1) is chronic idiopathic pain. We used targeted editing of Nf1 in rats to provide direct evidence of a causal relationship between neurofibromin, the protein product of the Nf1 gene, and pain responses. Our study data identified a protein-interaction network with collapsin response meditator protein 2 (CRMP2) as a node and neurofibromin, syntaxin 1A, and the N-type voltage-gated calcium (CaV2.2) channel as interaction edges. Neurofibromin uncouples CRMP2 from syntaxin 1A. Upon loss/mutation of neurofibromin, as seen in patients with NF1, the CRMP2/Neurofibromin interaction is uncoupled, which frees CRMP2 to interact with both syntaxin 1A and CaV2.2, culminating in increased release of the pro-nociceptive neurotransmitter calcitonin gene-related peptide (CGRP). Our work also identified the CRMP2-derived peptide CNRP1, which uncoupled CRMP2's interactions with neurofibromin, syntaxin 1A, as well as CaV2.2. Here, we tested if CRISPR/Cas9-mediated editing of the Nf1 gene, which leads to functional remodeling of peripheral nociceptors through effects on the tetrodotoxin-sensitive (TTX-S) Na + voltage-gated sodium channel (NaV1.7) and CaV2.2, could be affected using CNRP1, a peptide designed to target the CRMP2–neurofibromin interface. The data presented here shows that disrupting the CRMP2–neurofibromin interface is sufficient to reverse the dysregulations of voltage-gated ion channels and neurotransmitter release elicited by Nf1 gene editing. As a consequence of these effects, the CNRP1 peptide reversed hyperalgesia to thermal stimulation of the hindpaw observed in Nf1 -edited rats. Our findings support future pharmacological targeting of the CRMP2/neurofibromin interface for NF1-related pain relief.